PENDEKATAN FUNGSIONALISME STRUKTURAL TALCOTT PERSON UPAYA MELESTARIKAN TRADISI KENDURI SKO MASYARAKAT KERINCI - Pritania, Nayes; Sandora, Lisna (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2024)
As time progresses, there are more challenges faced. One of these challenges is the increasingly modern globalization, which can easily lead to the loss of existence of a culture and make it vulnerable to extinction.  This research has two main objectives. First, to understand the existence of the "kenduri sko" tradition within the Kerinci community. This "kenduri sko" tradition is crucial for the Kerinci people, not only as a culture passed down through generations but also because it embodies valuable qualities and has become an identity for the Kerinci community. Second, the researcher's awareness of the importance of preserving and maintaining the continuity of this culture. The effort proposed to preserve it is by implementing Talcott Parsons' structural functionalism theory. The methods employed by the researcher are literature review and descriptive methods. The findings indicate that "kenduri sko" carries significant local wisdom, aligning with the goals of structural functionalism theory, which aims for integration. Every member of the Kerinci community, whether ordinary citizens, "anak batino" (women), government officials, religious scholars, "depati" and "ninik mamak," or government officials, has their respective roles and functions in the execution of "kenduri sko." Some aspects of "kenduri sko" have evolved positively in line with the times. Thus, if the values, roles, and functions can be understood and implemented effectively and can adapt to modern developments, the "kenduri sko" tradition can be preserved.